Pengaruh Penggunaan Media Audiovisual Terhadap Kemampuan Membaca Permulaan Anak Usia 4-6 Tahun Pada Kelompok B di Tk Negeri Pembina Siborong-Borong (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The aim of the author in conducting this research was to be able to understand the influence of the use of audiovisuals on the beginning reading abilities of children aged 4 to 6 years in group B at the Siborong-borong State Kindergarten. The quantitative method is the method used by the author. The author's sample was children aged 4 to 6 years with a total of 44 people. The results of data analysis show that there is a positive and significant influence of the use of audiovisual media on the beginning reading abilities of children aged 4-6 years in Group B at the Pembina Siborongborong State Kindergarten: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.538 > rtable(a=0.05,n=44) = 0.297, thus it is known that there is a positive relationship between variable X and variable Y. b) Test the relationship The significant value obtained is tcount= 4.134 > ttable(a=0.05,dk=n-2=42)=2.021, thus there is a significant relationship between variable . Thus Ha is accepted and H0 is rejected.